70 EFFECTS OF LOW OXYGEN SATURATION LIMITS ON CLOSURE OF DUCTUS ARTERIOSUS IN EXTREMELY LOW BIRTH WEIGHT INFANTS. Issue 1 (1st January 2007) - Noori, S.; Patel, D.; Zamani Noor, S.; Friedlich, P.; Seri, I.; Siassi, B.; Ramanathan, R.
Abstract : Background: Extremely low birth weight (ELBW) infants are at increased risk for developing retinopathy of prematurity (ROP) and lower oxygen saturation limits have decreased the incidence of severe ROP. Although oxygen is known to constrict the ductus arteriosus (DA), a localized ductal wall tissue hypoxia is required for permanent closure of the DA. Objective: To compare the incidence of patent ductus arteriosus (PDA) and the need for ductal ligation in ELBW infants before and after implementation of lower oxygen saturation limits. Methods: Retrospective data analyses of prospectively collected data on ELBW infants admitted to one of our neonatal intensive care units 4 years before and after the implementation of a new oxygen saturation limit for prevention of ROP were included in the study. Patients with a gestational age of less than 23 weeks were excluded. During the period prior to the implementation of the lower saturation limits (83-89%), ELBW infants requiring oxygen were maintained at oxygen saturations of 89 to 94%. Results: A total of 186 ELBW infants comprised our study population. There were 108 patients (birth weight [BW] 744 ± 125 g, gestational age [GA] 25.8 ± 1.6 weeks) before and 78 patients (BW 777 ± 128 g, GA 25.9 ± 1.7 weeks) after the implementation of the lower oxygen saturation limit protocol. There was a significant reduction in the incidence of stage III or greater ROP (26% vs 11%, p = .015). However, the incidence of PDA (52% vs 55%) and ductal ligation (41% vs 42%) was unchanged. Conclusions: The use of the lower oxygen saturation limits in ELBW infants resulted in a significant reduction in severe ROP without significantly impacting the incidence of PDA or the need for DA ligation.